Rural youth and employment in Ethiopia - Schmidt, Emily; Bekele, Firew (International Food Policy Research Institute, 2016)
This paper examines labor diversification in Ethiopia, focusing on youth, and explores current conditions that youth face in both the agricultural and non-farm labor markets. Using data from the Ethiopia Socioeconomic Survey (ESS) and the National Labor Force Survey (NLFS), we explore current trends in labor diversification, along with youth non-farm engagement in rural and small towns. We find that youth (ages 25 to 34 years) have a greater probability of working in non-farm enterprises compared to mature individuals (age 35-64). However, wage labor opportunities remain scant in rural Ethiopia. The majority of individuals working in non-farm employment are engaged in small-scale trade activities.